2006
DOI: 10.1007/s10544-006-9031-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading of rigid intramuscular implants

Abstract: Several groups are developing different versions of a new class of leadless, permanently implanted electronic devices with a size and form factor that allows them to be injected into muscles (BIONs TM ). Their circuitry is protected from body fluids by thin-walled hermetic capsules made from rigid and brittle materials (glass or ceramic) that include feedthroughs to their electrodes. These packages experience repetitive stresses from the very contractions that they excite. We here provide a worst-case analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Similarly, the first generation BION microstimulator used a glass housing to enhance RF transparency, but found that the housing was prone to fracture after repeated bending stress due to muscle contraction (Fig. 2b) (Loeb, et al, 2007). Careful mechanical design was able to improve the strength of the BION glass housing; subsequent versions of the implant utilized a ceramic housing with a 7x improvement in bending strength (Kane, et al, 2011).…”
Section: Classical Ceramic Packaging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the first generation BION microstimulator used a glass housing to enhance RF transparency, but found that the housing was prone to fracture after repeated bending stress due to muscle contraction (Fig. 2b) (Loeb, et al, 2007). Careful mechanical design was able to improve the strength of the BION glass housing; subsequent versions of the implant utilized a ceramic housing with a 7x improvement in bending strength (Kane, et al, 2011).…”
Section: Classical Ceramic Packaging Methodsmentioning
confidence: 99%
“…In cochlear implants, all-alumina housing was explored by Cochlear Ltd, MED-EL, and Neurolec, but due to the large amount of exposed area, the housings were vulnerable to failure due to mechanical impact [55]. Similarly, the first generation BION microstimulator used a glass housing to enhance RF transparency, but found that the housing was prone to fracture after repeated bending stress due to muscle contraction (figure 2) [56]. Careful mechanical design was able to improve the strength of the BION glass housing; subsequent versions of the implant utilized a ceramic housing with a 7× improvement in bending strength [57].…”
Section: Classical Ceramic Packaging Methodsmentioning
confidence: 99%
“…10). No injury was suffered by the patients, but this discovery triggered a voluntary suspension of clinical trials and effort shifted to root-cause analysis [55]. The failures were attributed to stress risers appearing from the application of repetitive shear forces between the electrodes and the glass body.…”
Section: Clinical Testsmentioning
confidence: 99%
“…Broken BION capsules move with wrist flexure, but patients reported no symptoms except loss of function[55]. Reproduced with permission from Springer Science+Business Media: Biomedical Microdevices, Mechanical Loading of Rigid Intramuscular Implants, 2007;9: p902, Loeb,Fig 1.…”
mentioning
confidence: 99%
“…a) Cracked alumina casing in a cochlear implant due to mechanical impact of the head(Stöver & Lenarz, 2009). b) Broken intramuscular microstimulators encased in glass housing due to bending stresses from muscle contractions(Loeb, et al, 2007).…”
mentioning
confidence: 99%